A consumer perspective of the circular economy: an empirical investigation through structural equation modelling - Jan, Muhammad Tahir (2020)
The growing concerns about environmental decimation have given rise to a new approach called “The Circular Economy”, with the focus on introducing innovative and new methods of responsible production, consumption, and disposal. This is also aligned with the United Nations Sustainable Development Goals (UN SDG), particularly goal number twelfth where the focus is on responsible production and consumption. In marketing, there is only a limited number of studies conducted to explore and investigate the circular economy from a marketing perceptive. The present study, therefore, attempts to investigate some inevitable factors of circular economy with their impact on consumer behaviour. More specifically, five important factors (convenience/ availability, cost/ financial incentive, environmental impact, brand image/ design, and customer services/ supportive relationships) are extracted from the literature to examine their effect on consumer behaviour. For this purpose, data were collected from 311 consumers of circular products. Complex statistical techniques like exploratory factor analysis and structural equation modelling with confirmatory factor analysis and hypotheses testing were used to analyse the data. The findings revealed that convenience/ availability, cost/ financial inventive, and environmental impact are the most influential factors followed by customer service/ supportive relationships and brand image/ design. These findings will help policy-makers devise strategies that are not only sustainable and aligned with the philosophy of circular economy but will also ensure positive consumer behaviour.